Delineating the source of resistance to bean common mosaic virus (BCMV) and bean common mosaic necrosis virus (BCMNV) in common bean (Phaseolus vulgaris) cultivars of Jammu and Kashmir, a North-Western Himalayan region - Meghanath, Dasari; Wani, Sumiah; Bashir, Sabiya; Rashid, Shahjahan; Javaid, Andleeb; Dar, Zahoor Ahmad; Wani, Shabir Hussain; Sofi, Parvaze A.; Ali, Gowhar; Hamid, Aflaq (Frontiers in Microbiology, 2025)
Bean common mosaic virus (BCMV) and bean common mosaic necrosis virus (BCMNV) are among the most challenging constraints for common bean production in Northern states of India due to their easy transmission through aphids and seeds. Highly valuable Indian common bean varieties and landraces are more susceptible to BCMV and BCMNV and very few varieties exhibit resistance to these viruses. Resistance towards these viruses is governed by a single dominant (I) gene and a few recessive genes (bc-1, bc-2, bc-3, bc-4, bc-ud, and bc-ur). This study aims to identify common bean genotypes bearing multiple resistant genes, each working with a different mode of action. A total of 123 genotypes of common beans were mechanically inoculated with BCMV and BCMNV isolates and molecular markers (SW13, ROC11, BCMV-CAPS, ENM-FWe/Rve) were used to identify the presence of two major resistant genes (I and bc-3). Out of these, 23 genotypes were found phenotypically resistant to both viruses. Furthermore, molecular screening was performed in which 13 hypersensitive resistant genotypes bearing a single dominant gene (I) were confirmed through SW13 and BCMV-CAPS markers. Additionally, ROC11/420, ENMF/R markers identified 4 genotypes bearing the recessive (bc-3) gene conferring complete resistance to the virus without executing hypersensitive response (HR). A valuable gene combination of both I, bc-3 (Ibc-3, Host group-12) genes in 3 genotypes was also established in the screened germplasm. However, in 3 phenotypically resistant genotypes, neither the I gene nor bc-3 gene was identified. The virus accumulation in the resistant genotypes was also understood properly through a time course experiment in a qPCR assay. This extensive identification of resistant common bean genotypes against BCMV and BCMNV can be readily included in the common bean breeding program of the Northern states of India for virus resistance.